Genera, subgenera, species and subspecies of hard ticks (Acari: Ixodidae) described, named, renamed or given new rank by Paul Schulze (1887–1949) and their current status - Guglielmone, A. A.; Petney, T. N.; Mastropaolo, M.; Robbins, R. G. (Zootaxa, 2017)
The names for 19 genera, 17 subgenera, 150 species and 150 subspecies of Ixodidae described by Paul Schulze, names changed by him after the revision of certain taxa, new ranks for names originally described by other authors, a few lapsus calamorum and some incorrect names ascribed to Schulze by other workers are discussed. Two genera (Cosmiomma and Nosomma) are valid, but most of Schulze’s subgenera are difficult to assess because of the current disarray that prevails at this classificatory level in the Ixodidae. Thirty-six of 150 species names discussed by Schulze are considered valid herein (3 species of Amblyomma, 1 Bothriocroton, 1 Cosmiomma, 6 Dermacentor, 4 Haemaphysalis, 5 Hyalomma, 13 Ixodes, 1 Nosomma and 2 Rhipicephalus), while 28 are valid species epithets that are currently assigned to different genera (e.g., Acarus undatus was formerly classified in the genus Aponomma but is currently known as Bothriocroton undatum). Twenty-nine of these valid species names were authored by Schulze or Schulze & Schlottke. The remaining species names are mostly synonyms or names that are incertae sedis, nomen nudum or lapsus calamorum. The 150 subspecific names are treated as synonyms of valid species or as nomina nuda, nomina dubia, incertae sedis or lapsus calamorum. Many names used by Schulze have been synonymized based on sound systematic research, but the justification for synonymizing other names is occasionally weak. It will be important to take these names into account if, as has already happened, future molecular and morphological studies result in the reinstatement of Schulze names currently considered synonyms. This situation has particular relevance for Amblyomma geoemydae, the Amblyomma marmoreum species complex, Amblyomma testudinarium, Oriental species of Dermacentor, Hyalomma in general, Ixodes arboricola, Ixodes canisuga, Ixodes lividus, Ixodes trianguliceps and Ixodes uriae. In conclusion, the prolific contributions of Paul Schulze have their weak points —the many species and subspecies of Hyalomma described by him are unjustified as is the alleged worldwide distribution of the former genus Aponomma—but his perception of the complexity of the genus Dermacentor (under Indocentor) in the Oriental and Australasian Zoogeographic Regions, as well as his understanding of tick biodiversity in these regions constitute seminal scientific achievements.